Analysis of Virtual positions Management development Supporting Technology for initial Results of the Semester of Code - Vimal Kumar Stephen. K; V. Mathivanan (Institute of Advanced Engineering and Science, 2017)
This paper clarifies the Virtual Alliances for Learning Society (VALS) Project technological method to deal with bolster a virtual positions management development. Likewise, this paper demonstrates the first results of the viable piece of the venture, the Semester of Code, clarifying the recognized issues, the issues, the difficulties and a few activities to enhance the advancement of this sort of virtual positions programs. With a specific end goal to enable the readers to better understand the approach and its outcomes, the composition likewise portrays three of the principle virtual positions programs far and wide, in regards to both their association and innovative approach.